Acute Iloprost Inhalation Improves Right Ventricle Function in Pulmonary Artery Hypertension: A Cardiac Magnetic Resonance Study - Li, Jing-Hui; Zhang, Hong-Da; Wang, Zhen-Zhen; Lu, Qing-Qing; Li, Dong; Lian, Tian-Yu; Lv, Zi-Chao; Jiang, Xin; Wu, Yan; Ye, Jue; Zhao, Shihua; Yang, Zhenwen (Frontiers in Pharmacology, 2019)
Background: Right ventricle (RV) function is among the most important prognostic factors for pulmonary arterial hypertension (PAH) patients. Inhaled iloprost, an inhaled member of prostacyclin family, is effective for the treatment of severe PAH and acute RV failure. However, the acute effects of iloprost on RV physiology have not been thoroughly explored in the past. Material and Methods: This prospective study involved 69 incident PAH patients, including 23 idiopathic PAH (IPAH), 26 PAH associated with connective tissue disease (CTD-PAH) and 20 PAH associated with congenital heart disease (CHD-PAH). All patients underwent both right heart catheterization and cardiac magnetic resonance imaging at baseline and 20 min after 5 µg iloprost inhalation. Results: Acute iloprost inhalation reduced PVR from 13 ± 7 to 10 ± 6 Wood U (P < 0.001), increased RV ejection fraction (RVEF) from 31 ± 11 to 35 ± 12 % (P <0.001), increased RV stroke volume from 53 ± 21 to 57 ± 22 ml (P < 0.001) and decreased RV end-diastolic volume from 179 ± 67 to 172 ± 69 ml (P < 0.001). Acute iloprost inhalation induced RVEF improvement was correlated with the degree of PVR reduction (P <0.001) in IPAH patients, but not in CTD-PAH or CHD-PAH patients. Conclusions: Acute iloprost inhalation improved RVEF, RV stroke volume and decreased RV volume in IPAH and CTD-PAH patients. Iloprost induced RVEF increase was proportional to PVR reduction in IPAH, but not in CTD-PAH or CHD-PAH patients.